The labor market in Australia, 2000–2016 - Garry Barrett (IZA World of Labor, 2018)
Since 1991, the Australian economy has experienced sustained economic growth. Aided by the commodities boom and strong public finances, the Australian economy negotiated the global financial crisis without falling into recession. Over this period there were important structural changes, with increasing labor force participation among the elderly and the continuing convergence of employment and unemployment patterns for men and women. However, some recent negative trends include a rise in unemployment, especially long-term unemployment, a deteriorating youth labor market, and a stagnant gender earnings gap.
Keywords: J21; J30; E24; 330; unemployment; real earnings; Australia